Social Justice for Public Health: The COVID-19 Response in Portugal - Cordeiro-Rodrigues, Luís (J Bioeth Inq, 2020)
The COVID-19 pandemic requires emergency policies to be put in place in order to avoid a global health catastrophe. At the same time, there has been an increasing preoccupation that argues urgent policies for public health neglect social justice. By looking at Portugal’s successful confinement case during the early stages of the pandemic, I argue that ethically driven social justice policies are not just compatible but also an instrumentally important element in addressing this pandemic in an effective way. The Portuguese case study suggests that enhancing social justice towards socio-economically vulnerable groups correlates with the prevention of the spread of COVID-19; these benefits to public health can be explained by the fact that those policies create social distancing and less exposure to the COVID-19 virus and other contagious diseases and also remove disincentives to the use of healthcare services.